Variations in The Competence of Students at SMP N 2 Gondangrejo in Writing Field Trip Report - Mutia Dewi Anggraini; M Markhamah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the variation in the competence of students at SMP N 2 Gondangrejo in writing field trip reports in terms of content completeness. This study uses a qualitative descriptive approach. The data collection techniques used in this study are documentation and reading techniques. The analysis techniques in this study include data reduction, data presentation, and conclusion drawing. Data validity in this study uses source and theory triangulation. Based on the analysis results, it can be concluded that the ability of students at SMP N 2 Gondangrejo in writing field trip reports still requires guidance. This is because none of the students' field trip reports fulfilled the aspect of completeness of content. The field trip reports of students at SMP N 2 Gondangrejo can be grouped into: (1) incomplete because one aspect is missing, (2) incomplete because three aspects are missing, (3) incomplete because four aspects are missing, and (4) incomplete because five aspects are missing.